(untitled) (Patan Prospective Journal, 2025)
Dengue is a viral infection transmitted by female Aedes aegypti and Aedes albopictus mosquitoes (Vasilakis et al., 2011). The causative agent, dengue virus (DENV), belongs to the genus Flavivirus of the Flaviviridae family, which comprises single-stranded RNA viruses (Gould et al., 2008). DENV has four main serotypes: DENV-1, DENV-2, DENV-3, and DENV-4(Takasaki et al., 2008). Most dengue infections (up to 60%) are self-limiting (Bhatt et al., 2013), characterized by acute fever, frontal headache, vomiting, myalgia, joint pain, and a macular skin rash (Simmons et al., 2012). This report lists and examines dengue cases in Birgunj Metropolitan City, Nepal, based on a dataset of 26 confirmed patients. Among them, young adults aged 20–30 years were found to be the most affected age group, with 13 patients, which is 50% of cases, suggesting elevated exposure due to occupational and behavioral factors. Based on gender, males were found to be more affected compared to females, with 19 patients, likely linked to lifestyle patterns and outdoor activity. Temporally, cases were concentrated in the months of Falgun (n=14) and Chaitra (n=12), indicating active transmission during the late dry season and differences seen due to the weather patterns.